KAJIAN PENDEKATAN VISUAL IKLAN PADA INSTAGRAM - Rizki Yantami Arumsari; Jiwa Utama (LPPM Institut Bisnis dan Teknologi Indonesia, 2018)
Social media technology as a medium of communication has progressed quite rapidly and has a significant role for human life until 2018. One of the role of social media that feels quite influential is to help businesses in advertising their products. Although Instagram provides Ads features for business people, but they do not always use the Ads feature to advertise their products. Most of them just use personal accounts and display photos of their products to advertise. The technique they use in advertising is pure photography, digital imaging, and photography combined with text. Despite having a technique quite different from conventional advertising in general, the businessman can still advertise his product even very helpful in the sale of its products. It will provide a different persuasive approach for those who see it. Through observation, literature studies and interviews, attempts are made to elaborate the persuasiveness resulting from the visual approach commonly found in Instagram. The results of this study indicate that visual advertising using photography approach but without mentioning tagline that reflects positioning as product differentiator. The approach is used based on the main needs of social media Instagram which prioritizes the photo as a medium of communication.